Stock return prediction using financial ratios / Azlizan Wang Kee - Wang Kee, Azlizan (2015)
This study aims to give the evidence of whether financial ratios are able predict the future stock return in Malaysian Stock Market. Four variables are used as a predictor of future stock return which are the Book to Market Ratio (BTM), Dividend Yield (DY), Earning per Share (EPS), and Price to Earnings Ratio (PE). This study covers the period of 2010 until 2014 using quarterly data of 24 listed companies in Bursa Malaysia Stock Exchange from Industrial Product Industry. Results from the multiple regressions analysis shows that only BTM, DY, and PE are able to predict future stock return, as EPS is insignificant. In addition, DY has superior predictive power compared to the other variables.